The Bronte story (Oxford Bookworms 3) - Vicary, Tim (Oxford Univ. Press, 1997)
On a September day in 1821, in the church of a Yprshire village, a man and six children stood around a grave. They were burying a woman: the man's wife, the children's mother. The children were all very young, and within a few years the two oldest were dead, too. Close to the wild beauty of the Yorshire moors, the father brought up his young family. Branwell died while ha has still a young man, but the three sisters who were left had an extraorninary gift. They could write marvellous stories - Jane Eyre, Wurthering Heights, The Tenant of Wildfell Hall... But Charlotte, Emily, and Anne Bronte did not live grow old or to enjoy their fame. Only Their father was left, alone with his memories.